Influence of ZnO:Al, MoO3 and PEDOT:PSS on efficiency in standard and inverted polymer solar cells based on polyazomethine and poly(3-hexylthiophene). (10th February 2016) - Iwan, Agnieszka; Palewicz, Marcin; Tazbir, Igor; Boharewicz, Bartosz; Pietruszka, Rafal; Filapek, Michal; Wojtkiewicz, Jacek; Witkowski, Bartłomiej Sławomir; Granek, Filip; Godlewski, Marek
Abstract: This paper is devoted to the development of standard and inverted polymer solar cells based on polyazomethine (PAZ-Car-TPA), poly(3-hexylthiophene) (P3HT) and [6, 6]-phenyl C61 butyric acid methyl ester (PCBM). We analyzed the influence of: (i) PEDOT:PSS or MoO3 as a hole transporting layer in standard devices, (ii) aluminum doping level (from 0 to 3.7%) in ZnO (obtained by atomic layer deposition, ALD) applied as an electron transporting layer in inverted solar cells and (iii) the method applied to obtain ZnO layer (ALD or sol-gel) on its photovoltaic properties. The best device configuration is ITO/AZO (3% Al)/P3HT:PCBM/MoO3 /Ag which exhibits a power conversion efficiency of 1.51% under about 100 mW/cm 2 AM 1.5 G simulated solar emission. Devices were additionally tested by electrochemical impedance spectroscopy. HOMO-LUMO levels of PAZ-Car-TPA and its mixture with HCl, H2 SO4, p-toluenesulfonic acid, PEDOT:PSS and water were analyzed by cyclic voltammetry and quantum mechanical calculations using Density Functional Theory method.